1986
DOI: 10.1128/jvi.60.3.950-959.1986
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of transcription in vitro from herpes simplex virus genes

Abstract: In vitro transcription assays were carried out by using as templates DNAs cut from the herpes simplex virus early glycoprotein D gene, the late glycoprotein C gene, the late VP5 gene, and the immediate-early ICP22 gene. Nuclear extracts from suspension cultures of uninfected HeLa cells effectively synthesized RNAs from genes of the immediate-early and delayed-early classes. To a lesser extent, the extracts also used DNAs cut from the late genes as templates. Transcription from the immediate-early gene was inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…we have previously shown that ICP4 (fraction VIII) stimulates the rate of in vitro RNA synthesis from viral DNA templates (1,48). In this study, we tested the response to ICP4 (fraction VIII) with templates from p5BS-A, pAgDCAT, and a fragment of the natural gD gene, AvaI-1 (33).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…we have previously shown that ICP4 (fraction VIII) stimulates the rate of in vitro RNA synthesis from viral DNA templates (1,48). In this study, we tested the response to ICP4 (fraction VIII) with templates from p5BS-A, pAgDCAT, and a fragment of the natural gD gene, AvaI-1 (33).…”
Section: Resultsmentioning
confidence: 99%
“…Template DNAs for in vitro transcription experiments were purified from low-melting-temperature agarose as previously described (48). pAgDCAT and pSBS-A were cleaved at the NdeI site in the vector DNA and the BalI site in the CAT gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the significance of the binding site in the DE promoter for the gD gene is of some interest. Pizer et al (47) have suggested that it has a positive effect from in vitro transcription studies, whereas Arsenakis et al (1) argue that there may be negative effects as well. However, in transient cotransfection assays the IE175-binding site in the gD promoter is not required for IE175 activation of gD-CAT activity (P. O'Hare and A. Haig, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…It binds to sequences in the promoter regions and transcribed noncoding regions of various HSV-1 genes as part of a protein complex (1,20,21,50,51,65), and recent evidence suggests that it may bind directly to DNA on its own (64). Partly purified preparations of ICP4 have also been found to stimulate transcription of HSV-1 early and late genes in vitro (1,73). However, it is not known whether direct binding of ICP4 is necessary for this transcriptional stimulation to occur.…”
mentioning
confidence: 99%